Effects of Subcortical Atrophy and Alzheimer’s Pathology on Cognition in Elderly Type 2 Diabetes: The Alzheimer’s Disease Neuroimaging Initiative Study - Zhang, Wen; Lu, Jiaming; Qing, Zhao; Zhang, Xin; Zhao, Hui; Bi, Yan; Zhang, Bing, the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2022)
Background: Subcortical atrophy and increased cerebral β-amyloid and tau deposition are linked to cognitive decline in type 2 diabetes. However, whether and how subcortical atrophy is related to Alzheimer’s pathology in diabetes remains unclear. This study therefore aimed to investigate subcortical structural alterations induced by diabetes and the relationship between subcortical alteration, Alzheimer’s pathology and cognition. Methods: Participants were 150 patients with type 2 diabetes and 598 propensity score-matched controls without diabetes from the Alzheimer’s Disease Neuroimaging Initiative. All subjects underwent cognitive assessments, magnetic resonance imaging (MRI), and apolipoprotein E (ApoE) genotyping, with a subset that underwent amyloid positron emission tomography (PET) and cerebrospinal fluid (CSF) assays to determine cerebral β-amyloid deposition (n = 337) and CSF p-tau (n = 433). Subcortical structures were clustered into five modules based on Pearson’s correlation coefficients of volumes across all subjects: the ventricular system, the corpus callosum, the limbic system, the diencephalon, and the striatum. Using structural equation modeling (SEM), we investigated the relationships among type 2 diabetes, subcortical structural alterations, and AD pathology. Results: Compared with the controls, the diabetic patients had significant reductions in the diencephalon and limbic system volumes; moreover, patients with longer disease duration (> 6 years) had more severe volume deficit in the diencephalon. SEM suggested that type 2 diabetes, age, and the ApoE ε4 allele (ApoE-ε4) can affect cognition via reduced subcortical structure volumes (total effect: age > ApoE-ε4 > type 2 diabetes). Among them, age and ApoE-ε4 strongly contributed to AD pathology, while type 2 diabetes neither directly nor indirectly affected AD biomarkers. Conclusion: Our study suggested the subcortical atrophy mediated the association of type 2 diabetes and cognitive decline. Although both type 2 diabetes and AD are correlated with subcortical neurodegeneration, type 2 diabetes has no direct or indirect effect on cerebral amyloid deposition and CSF p-tau.